IMPLEMENTASI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG IZIN POLIGAMI DI PENGADILAN AGAMA BUKITTINGGI (Studi Kasus Perkara Nomor 081/Pdt.G/2013/PA.Bkt dan Perkara Nomor 0328/Pdt.G.2015/PA.Bkt) - Handayani, Setia; Alfin, Aidil; Daipon, Dahyul (Alhurriyah, 2019)
The provision of polygamy as regulated in Law Number 1 of 1974 states that a husband who is going to polygamy must meet alternative and cumulative requirements. Without the fulfillment of the two conditions mentioned, the application for polygamy will be rejected by the judge. But in reality, the Bukittinggi Religious Court differed in ruling two polygamy cases which both met cumulative requirements and did not meet alternative conditions. In the first case case Number 081 / Pdt.G / 2013 / PA.Bkt the judge has accepted the request for polygamy, while in the second case case Number 0328 / Pdt.G / 2015 / PA.Bkt. the judge did not accept (NO) the case. The implementation of Law Number 1 of 1974 concerning polygamy permits in the Bukittinggi Religious Court is not absolute, the consideration of judges who receive and examine cases Number 081 / Pdt.G / 2013 / PA.Bkt is the emergence of mudharat if the case is rejected even though the alternative conditions are not met . Whereas the judge examining case 0328 / Pdt.G / 2015 / PA.Bkt was based on the provisions of article 4 of Law Number 1 of 1974 rejecting the case because it did not meet alternative conditions. Due to the non-fulfillment of alternative conditions by the Petitioner, the request for polygamy permit had a formal defect. For this reason, the panel of judges no longer needs to examine the subject matter.